The Role of Teachers in Preventing Bullying Cases in Elementary Schools - Erwin Eka Saputra (FKIP UNSULTRA, 2025)
Bullying cases in elementary schools are serious problems that can affect children's physical, emotional, and social development. In this context, the role of teachers is very important in creating a safe and inclusive environment for all students. This study aims to analyze the existing literature on the role of teachers in preventing bullying in elementary schools. Various studies show that teachers have a responsibility to identify, respond to, and prevent bullying behavior through a preventive and responsive approach. The approaches used include strengthening school policies, character education, and social skills training for students. In addition, teachers also need to create open communication with students, parents, and the community. The results of this literature analysis highlight the importance of improving teacher skills in handling bullying cases, as well as the need for collaboration between various related parties to create an environment free from bullying. It is hoped that this study can provide insight into concrete steps that can be taken by teachers in efforts to prevent bullying in elementary schools.